Influence of Value Added Tax and Sales Tax on Luxury Goods on Purchase Power Using a Systematic Literature Review (SLR) Approach - Fatimah, Siti; Riyandi, Riyandi; Situngkir, Tiarlina; Deva, Kekey Mahesa (Jurnal Ilmiah Wahana Pendidikan, 2025)
Taxes are one of the government's largest sources of funding. The automotive industry is one of the sectors that generates the largest amount of tax. Every vehicle and electronic product is subject to VAT, and those included in the luxury goods category will be subject to PPNBM. The focus of this study is the effect of taxes on consumer purchasing power. For this writing, Systematic Literature Review (SLR) was used; SLR reviews articles in a systematic and planned manner, increasing the depth of examination related to VAT and PPNBM. The research results show that, simultaneously, the variables VAT (X1) and PPnBM (X2) influence consumer purchasing power (Y). VAT (X1) has a significant positive effect on buyers' desire to buy a luxury good. The PPnBM variable (X2) has a significant influence on consumer purchasing power for luxury goods. When the tax imposed is higher, of course, this means that the luxury goods owner will gain social status and prestige. This shows that people have the ability and are willing to pay taxes on luxury goods so that they can be respected for having high-quality products.